El principio de oportunidad en el proceso penal de menores (Análisis comparado de los Ordenamientos colombiano y español) (2009)
The juvenile criminal process has been conceived as a special kind of process used to react to an action considered a less serious crime. This article aims to demonstrate that, although the recognition that has been done on the nature of the criminal proc